Analysis of the Physical and Mechanical Behavior of Soil Reinforced with Banana Fibers - Schreiber Robles, Favio Osmar; Muñoz Pérez, Socrates Pedro; Garcia Chumacero, Juan Martin; Sanchez Diaz, Elver; Damiani Lazo, Carlos Arturo; Malpartida Iturregui, Juan De Dios; Ruiz Pico, Angel Antonio; Diaz Ortiz, Edwin Adolfo; Rodríguez Lafitte, Ernesto Dante; Bernal Izquierdo, Ana Paula (Ingeniería, 2025)
Context: Soils reinforced with natural fibers such as banana fibers (BF) constitute a promising alternative for improving the geotechnical properties of the soil, especially in rapidly growing urban contexts like Peru. Methods: This study was structured into four stages: the extraction and preparation of soil samples; the evaluation of the physical characteristics of the fibers; mixing with proportions of 0.5, 1, 1.5, and 2% BF relative to the soil dry weight; and physical and mechanical tests to assess the effects on geotechnical properties. Results: The addition of 1% BF optimized the properties of the modified soil: the maximum dry density remained stable, the California bearing ratio increased by 5.95%, and the unconfined compressive strength increased by 23.81% compared to natural soil. Conclusions: The use of BF-treated soil meets the local standards for application in infrastructure such as roads and pavements, thus promoting sustainable construction practices and contributing to the development of resilient and environmentally responsible infrastructure.